Pengujian Theory of Trying pada Konteks Higher Level Goal dan Lower Level Goal - Suroso, Agus (Universitas Brawijaya, Indonesia, 2009)
The research is aimed to test Theory of Trying in different hierarchy of goals. The effort in mastering English represents higher level goal and student behavior in learning the next subject represents lower level goal. Elicitation study is conducted to find out salient belief, which is used to construct questionnaire. The total number of respondent is 117, drawn from student at LBPP-LIA Yogyakarta and Faculty of Economics Unsoed. The findings show that the attitude toward success significantly influence the attitude toward trying at higher and lower level goal. Whereas the attitude toward failure insignificantly influence the attitude toward trying both in lower level and higher level goal. The results also indicate that student intention at LIA to finish their study more influence by external motivation, whereas the student intention in trying to learn the next subject more influence by self awareness.